GE_GERICHTE C/17540/2017 vom 11. Juni 2019 - GE Cour de justice (2019)
ACTION EN CONTESTATION;PROPRIÉTÉ PAR ÉTAGES;VALEUR LITIGIEUSE;ASSEMBLÉE DES COPROPRIÉTAIRES;NULLITÉ;UNANIMITÉ | CC.712.letm; CC.648.al2; CC.647.al1.letb